EXPLORING THE ROLE OF DIGITAL MEDIA IN LEARNING L2: A CASE STUDY AT SECONDARY LEVEL IN D G KHAN - Muhammad Nasir; Aqsa Bashir; Nida Tahir Khan; Mujtaba Muhammad Hashmi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
Digital media is an important tool in education, especially for teaching and learning English as a Second Language (ESL) all over the world. Digital media is an umbrella term for educational media that is based on the Internet, computers, and mobile devices. The current study uses a quantitative method to find out how digital media affects both learning and teaching a second language. The purpose of this study is to look into how digital educational media can be used to teach and learn English as a second language at the secondary level in DG Khan. 100 secondary school students participated overall. The software Statistics Package for Social Sciences (SPSS) was used to look at the data. The questionnaire was measured on a Likert scale. Questionnaire and tests were used to collect the data. Getting to know how ESL students in school use digital media could help teachers figure out how to make digital media a better way for students to learn. Digital educational media used to teach an English language are categorized by what they do and how they help students learn. They can be narrative, interactive, adaptive, communicative, or productive. The main advantage of using digital media in education is that it can get students more involved. It also gives students a lot of tools to help them work through hard ideas. Digital instruction makes it easier to understand things that are hard to understand in other ways. This study will show how digital media can help students become more stable and improve their academic performance as they learn. The information for this study taken from the district D.G. Khan. The results show how students act when they learn and teach with the use of digital media, as well as the methods used in learning and teaching.